Effect of pH on okara protein-carboxymethyl cellulose interactions in aqueous solution and at oil-water interface. (April 2021) - Cai, Yongjian; Huang, Lihua; Tao, Xia; Su, Jiaqi; Chen, Bifen; Zhou, Feibai; Zhao, Mouming; Zhao, Qiangzhong; Van der Meeren, Paul
Abstract: The physicochemical and interfacial properties of Okara protein (OP) are susceptible to be affected by various factors. In this respect, the role of inter- and intramolecular interactions between OP and carboxymethyl cellulose (CMC) were explored by in situ experiments. OP/CMC aqueous mixtures, containing 1.0 wt% OP and 0–0.5 wt% CMC, were prepared at pH 7.0 and 4.0. Subsequently, their physicochemical properties, interactions, and interfacial adsorption were comparatively characterized. OP formed larger aggregates at lower pH as confirmed by the visual appearance. The addition of CMC reduced the surface hydrophobicity and increased viscosity of OP/CMC mixtures regardless of pH. CMC increased the hydrodynamic diameter of mixtures at pH 7.0, while it led to more negatively-charged complexes with decreasing size at pH 4.0. Noticeably, the results regarding the interfacial pressure, adsorption kinetics and interfacial dilatational viscoelastic properties presented three remarkable phenomena: Low concentrations of CMC hardly affected the initial interfacial performance of OP at pH 7.0, whereas the latter was greatly reduced at high CMC concentrations. Moreover, high CMC concentrations appropriately reinforced the interfacial performance of OP at pH 4.0. Graphical abstract: Image 1 Highlights: Carboxymethyl cellulose (CMC) reduced okara protein (OP) aggregation and enhanced its dispersity under acidic pH. OP/CMC mixtures exhibited stronger electrostatic repulsions at pH 4.0 than pH 7.0. CMC resulted in decreased surface hydrophobicity of OP/CMC mixtures. Relatively compact interfacial layers of OP/CMC mixtures were formed at pH 4.0.